DISIPLIN KERJA DALAM MEMEDIASI PENGARUH KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP PRODUKTIVITAS KERJA PEGAWAI - Bambang Priyanto; Woro Utari; Indra Prasetyo (Fakultas Ekonomi dan Bisnis Universita Wijaya Putra Surabaya, 2024)
The aim of this research is to describe and test and analyze the influence of compensation, work discipline which mediates compensation and work discipline which mediates organizational culture on the work productivity of BPBD Bojonegoro Regency employees. This research was carried out at the Bojonegoro Regency Regional Disaster Management Agency (BPBD) with a population of 48 people, then the sample was 48 people using a saturated sample. This research uses Structural Equation Modeling (SEM) data analysis techniques, using the Partial Least Square (PLS) approach. The research results showed that compensation, organizational culture, work discipline of Bojonegoro Regency BPBD employees were in the high category while the work productivity of Bojonegoro Regency BPBD employees was in the very high category. Compensation has a significant effect on work discipline, Organizational culture has a significant effect on work discipline, Work discipline has a significant effect on work productivity, Compensation has a significant effect on work productivity, Organizational culture has a significant effect on productivity, Work discipline can mediate a significant effect on compensation on work productivity, work discipline can mediate culture.